2018
DOI: 10.1111/1751-7915.13265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cryopreservation and lyophilization on viability and growth of strict anaerobic human gut microbes

Abstract: SummaryStrict anaerobic gut microbes have been suggested as ‘next‐generation probiotics’ for treating several intestinal disorders. The development of preservation techniques is of major importance for therapeutic application. This study investigated cryopreservation (−80°C) and lyophilization survival and storage stability (4°C for 3 months) of the strict anaerobic gut microbes Bacteroides thetaiotaomicron, Faecalibacterium prausnitzii, Roseburia intestinalis, Anaerostipes caccae, Eubacterium hallii and Blaut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 56 publications
3
88
0
Order By: Relevance
“…A previous study reported that following 6 months of frozen storage of stools in 10% glycerol, CFU counts of six bacterial groups (bifidobacteria, Escherichia coli, total coliforms, lactobacilli, total anaerobic bacteria, or total aerobes) were similar to baseline values (Costello et al, 2015). Similarly, Bircher et al (2018) showed that the gut commensal Bacteroides thetaiotaomicron (phylum Bacteroidetes) was resistant to cryopreservation for 3 months in terms of CFU counts and membrane integrity. Another study, based on a PMA treatment combined with qPCR, showed a reduced overall viability but no significant changes in composition of viable microbiota frozen fecal samples (Papanicolas et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
“…A previous study reported that following 6 months of frozen storage of stools in 10% glycerol, CFU counts of six bacterial groups (bifidobacteria, Escherichia coli, total coliforms, lactobacilli, total anaerobic bacteria, or total aerobes) were similar to baseline values (Costello et al, 2015). Similarly, Bircher et al (2018) showed that the gut commensal Bacteroides thetaiotaomicron (phylum Bacteroidetes) was resistant to cryopreservation for 3 months in terms of CFU counts and membrane integrity. Another study, based on a PMA treatment combined with qPCR, showed a reduced overall viability but no significant changes in composition of viable microbiota frozen fecal samples (Papanicolas et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
“…Lyophilization and cryopreservation can impair growth and can lead to lethal damage for a certain fraction of preserved bacterial cells, clearing niches for more-resistant taxa that are less competitive in fresh microbiota (51). The levels of tolerance of freezing and drying differ greatly between different anaerobic gut microbes (34) and might explain the observed shifts. Previous preservation studies demonstrated that Gram-positive bacteria have an advantage over Gram-negative bacteria in surviving lyophilization (52,53).…”
Section: Resultsmentioning
confidence: 99%
“…A storage period of 9 months was selected to represent the conditions suggested for storing fecal material for fecal microbiota transplantation (FMT) (33). To improve preservation survival, the protectants sucrose and inulin (both 5% [wt/vol]) and combinations of sucrose and inulin (both 5% [wt/vol]) and glycerol (15% [vol/vol]), previously developed for stabilizing strict anaerobic gut microbes, were added for lyophilization and cryopreservation, respectively (34). Composition and metabolic activities of preserved plankM and sessM were evaluated in small-scale, strictly anaerobic batch cultures over 24 h, and the results were compared to those seen with batch cultures inoculated with fresh microbiota.…”
mentioning
confidence: 99%
“…Significantly higher cell density of culturable bacteria observed in sugar beet lyophilized roots can be attributed to high content of sucrose (Haankuku et al, 2015). This sugar acts as a natural osmoprotectant, allowing a better viability of microorganisms during lyophilization (Bircher et al, 2018). Another explanation of obtained results can be associated with higher ability of sugar beet endophytes to grow on solid medium.…”
Section: Discussionmentioning
confidence: 99%